Clinical-psychopathological analysis of current depressive disorders associated with suicidal behavior of women - Zelenska, Kateryna; Koltsova, Galina (ScienceRise: Medical Science, 2017)
Aim of research. Study of clinical and psychopathological features of depressive disorders associated with suicidal behavior in women in modern conditions Materials and methods of research. A comprehensive survey of 150 women aged 25-65 years was conducted who were diagnosed with depressive disorders: disorders of adaptation, in the form of depressive reaction (42.8%); moderate and severe depressive episode (35.1%), recurrent depressive disorder (22.1%) The main group consisted of 77 patients with signs of suicidal behavior, control - 73 patients without signs of suicidal behavior. Methods of research: clinical-anamnestic, psychodiagnostic, clinical-psychopathological Results. Distinguished anxiety (45.4% of the patients in the main and 32.1% of the control group), obesity (35.2% and 36.3% respectively), asthenia-apathetic (7.1% of the patients in the main and 18.2% of the control group) and melancholic (12.3% and 13.4% respectively) variants of depressive disorders. It is proved that women with depressive disorders combined with suicidal behaviour are adhered to high suicide risk, high anhedonia, severe anxiety and depression on the Hamilton scale, a large depressive episode on the Montgomery - Iceberg scale. For women with depressive disorders without signs of suicidal behaviour there was an average level of suicidal risk, high level of anhedonia, severe anxiety and depression on the Hamilton scale, a large depressive episode on the Montgomery - Iceberg scale Conclusions. 1. Women with depressive disorders with suicidal behaviour characterized by anxiety, tedious, asthenia-apathy and melancholy variants of depressive disorders. Patients with disturbing and timid variants of depression are characterized by a high level of suicidal risk. 2. Women with depressive disorders associated with suicidal behaviour there is a high level of suicidal risk, high anhedonia, severe anxiety and depression on the Hamilton scale, a large depressive episode on the Montgomery - Iceberg scale. 3. Prognostically significant in the formation of suicidal behaviour are disturbing and timid variants of depressive disorders, high rates of clinical anxiety and depression scales, high suicidal, obese suicidal anamnesis